Cost-benefit analysis of agroecological projects of one mini-dairy and two dairy production units of typical dairy farmers in Burkina Faso - Vall, Eric; Orounladji, Boko Michel; Ouattara, Songdah Désiré; Traore, Arahama; Sanogo, Souleymane; Sib, Ollo (2024)
Co-designing an Agroecological Business Model for the dairy value chain is a significant objective of the AEI project in Burkina Faso. This work is being carried out mainly within the WP3 of the AEI "Developing an inclusive economic model and financial strategies adapted to the Bobo-Dioulasso milk value chain". This document presents a quantitative cost-benefit analysis (CBA) concerning the integration of an agroecological technology (named agroecological packages) among three typical actors of the Bobo-Dioulasso dairy value chain, namely: The dairy production unit of an average agropastoral dairy farmer The dairy production unit of an average mini-dairy farm A mini-dairy using mainly local milk The general characteristics of these 3 types of actor are described by Sib et al. (2023). The CBA follows the guidelines presented in the practical guide proposed by the WP3 coordinators (Narjes et al., 2024).